Political Culture and Citizen Participation: Transiting from Political Space - Hernandez, Judith Josefina; Cordoba, Edgar; Chumaceiro, Ana Cecilia (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
Societies build their interpretation and representation on the different phenomena in their social, historical and political processes, so also the political culture contains a set of beliefs, ideas, myths, norms, which give it identity, values, and ends. Consequently, from the democratic culture, the citizen is encouraged to move in the public space, determined by actions, and practices. As a result of these relationships, participation mechanisms are institutionalized for the emancipation or defense of citizens against the role of the State that is domination. Characterizing the aspects that involve political culture, participation and citizen action in the democratic political space, is the central object of this dissertation. The systematic review, bibliographic, documentary, and critical analysis, facilitate the method and the achievement of results, it is concluded that democracy as a system of government is characterized by its factual expression of representation and participation, this implies a global interaction with negotiation of the scheme of interests between rulers and ruled.